Comparison of Carrying Angle of Elbow between Patients with and without Lateral Epicondylitis: An Observational Study - Sarik Kumar Shrestha; Manoj Kandel; Bhanubhakta Chalise; Keshav Mani Gautam; Sunil Panta; Pritam Chaudhary; Suman Subedi; Prakash Darjee (Journal of Nepal Medical Association)
Introduction: Lateral epicondylitis is a common cause of elbow pain, characterized by pain on the lateral side of the elbow joint. Its multifactorial etiology may result from repetitive micro-trauma, overuse of the forearm extensor muscles, use of vibrating tools, and anatomical variables causing lateral wear. In case of increased carrying angle of elbow, the course of extensor carpi radialis brevis during movement can be altered, thus increasing the tension on the extensor carpi radialis brevis tendon and increasing the risk for lateral epicondylitis. This study aims to find out the difference in carrying angle of elbow in patients with and without lateral epicondylitis. Methods: An observational cross-section study comparing carrying angle of elbow in patient with and without lateral epicondylitis was performed after ethical approval from the Institutional Review Committee (Reference number: 080/081-019) Patients presenting who had undergone radiographic examination of the elbow were recruited in the study and divided into the lateral epicondylitis group and the normal group. The mean carrying angle of elbow in both groups was compared using the parametric test. Results: This study included 82 participants, with 41 participants in the lateral epicondylitis group and 41 participants in the normal group. The mean carrying angle of elbow among patients with lateral epicondylitis group was 14.35±1.4 degrees; and the normal group, it was 12.40±1.26 degrees (p<0.001). Conclusions: The carrying angle of elbow in patients with lateral epicondylitis was significantly more than those without lateral epicondylitis.